Audiovisual collection management deselection and preservation of audiovisual collections of selected private and religious school learning resource centers in Marikina City - Sala, Virgilio F. (Institute of Library and Information Science, University of the Philippines Diliman, 2002)
This research study investigated the status of deselection and preservation practices adopted for audiovisual collections if private and religious school learning Resource Centers in Marikina City. The study used the descriptive survey method of research. Structured questionnaire were used in data gathering. It was also designed to 1) find out if private and religious school Learning Resource Centers in Marikina City practice deselection and preservation of audiovisual collections; 2) to know if these centers have written policies with regard the deselection and preservation of audiovisual collections; 3) to determine the reasons for deselection and preservation of audiovisual materials; 4) to know the methods and criteria used in the deselection and preservations; 5) to identify the problems encountered by the school librarians in the deselection and preservation process; 6) to present and suggest some improvements necessary to overcome the problems in the deselection and preservation of audiovisual collections. Seventeen (17) school Learning Resource Centers in Marikina City were surveyed and these were the Learning Resource Center of Charis School; Gentle Angel Learning Center; Holy Trinity of St. Therese of the Child Jesus; Infant Jesus Academy; Kostka School; Maranatha Christian Academy; Marikina Catholic School; Marikina Christian Academy; Marist School; Mother of Divine Providence; Nativity of Our Lady Parochial School; Our Lady of Perpetual Succor School; Regent Christian Academy; Roosevelt College; St. Nicholas School; St. Scholastica's Academy and Victorial School Foundation.